A special cable resistant to extreme environments

The cables are solved in petroleum drilling environments by using a composite blending technology of modified ethylene-vinyl acetate copolymers with ellowite nanotubes, chlorosulfonated polyethylene rubber and polyurethane elastomers in the sheathing materials of special cables. The problems of insufficient oil resistance, wear resistance, aging resistance and tensile performance have significantly improved the overall performance of the cable.

CN118956051BActive Publication Date: 2025-02-25GUANGDONG AOTONG SPECIAL CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411433039.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-25
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Existing special cables face deficiencies in oil-resistant, wear-resistant, aging resistance and tensile properties in oil drilling environments, resulting in performance degradation and premature failure when used under harsh conditions.

Method used

Modified ethylene-vinyl acetate copolymer is used as the main component of the sheathing material, and the composite blending system is formed by introducing components such as Elosite nanotubes, chlorosulfonated polyethylene rubber and polyurethane elastomer to improve the The cables are oil-resistant, wear-resistant, aging-resistant and tensile properties.

Benefits of technology

The tensile strength of the cable sheath material is improved, the wear resistance and aging resistance are significantly enhanced, and the oil resistance performance optimization in oily environments are optimized, extending the service life and stability of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118956051B_ABST
    Figure CN118956051B_ABST
Patent Text Reader

Abstract

The present invention provides a special cable resistant to extreme environments, and relates to the technical field of special cables. The special cable resistant to extreme environments provided by the present invention comprises a sheath layer, an insulating layer and a conductive core from the outside to the inside in sequence; the sheath layer is made of a sheath material, and the sheath material comprises the following components by mass: 40-60 parts of modified ethylene-vinyl acetate copolymer, 35-90 parts of elastomer, 30-50 parts of modified filler, 15-25 parts of plasticizer, 3-8 parts of POE-g-GMA, and 0.5-27 parts of auxiliary agent. The special cable provided by the present invention has excellent oil resistance and wear resistance, as well as good aging resistance and tensile properties, and is suitable for producing special cables such as logging cables, oil production cables, and heating cables resistant to extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special cables, and in particular to a special cable resistant to extreme environments. Background Art

[0002] Special cables refer to cables with special purposes or used in special occasions, such as high temperature environment, strong corrosive environment, and special occasions that require fire resistance, explosion resistance, insect resistance, etc. The widespread use of special cables fills the gap in the demand for ordinary cables in various application fields. For example, flame-retardant cables and fire-resistant cables can maintain a certain operating time in fire or high temperature environments, providing valuable time for personnel evacuation and system safety; waterproof cables and anti-corrosion cables are specially designed for humid or highly corrosive environments to ensure stable operation of cables under harsh conditions; in addition, there are explosion-proof cables, radiation-resistant cables, etc., which can provide safety protection for specific dangers or special environments.

[0003] In the field of oil drilling, special cables for the oil industry mainly include logging cables, perforating cables, sonic oil recovery cables, heating cables and other types according to their uses. The particularity and harshness of the oil drilling operating environment pose many challenges to cable sheath materials. 1) Oil resistance: During logging or mining processes, cables are often required to serve in an oily environment. Oils can penetrate into the rubber, causing molecular mutual diffusion, changing the network structure of the vulcanized rubber, causing it to swell or even crack, resulting in a reduction and loss of the strength and other mechanical properties of the rubber. 2) Wear resistance: Special cables are in great demand in the oil field exploration, excavation, transportation and other process stages of oil drilling. The frequent movement, friction, extrusion or pulling of cables under various working conditions causes significant mechanical wear and premature failure. 3) Aging resistance: Oil wells usually need to operate continuously for a long time, and cables need to work continuously. In addition, oil wells may be frequently started and stopped during production, which will cause greater mechanical and electrical stress on the cables. Each start and stop will cause the cables to experience temperature changes, current shocks, etc., which will accelerate the aging of the cables. Therefore, higher requirements are placed on the aging resistance of special cable sheath materials. 4) Tensile performance: Most crude oil is thick and viscous, and has high adhesion to the surface of cable sheath materials, resulting in greater resistance during the pulling process; therefore, it is necessary to improve the tensile performance.

[0004] Petroleum oils are non-polar. Currently, the main sheath materials used for wires and cables in the petroleum industry are nitrile rubber, chloroprene rubber, acrylate rubber, hydrogenated nitrile rubber, polyvinyl chloride rubber, fluororubber, fluorosilicone rubber, etc. Among them, chloroprene rubber is resistant to acid and alkali, but has poor resistance to hydrocarbon oils and petroleum; acrylate rubber has excellent weather resistance but is not resistant to high temperature and hydrocarbon oil; polyvinyl chloride rubber has good wear resistance and can also resist oil, acid, alkali, bacteria, moisture and sunlight, but contains a large amount of chlorine, and produces some carcinogens and HCl gas when burned, causing serious harm to the environment; fluororubber and fluorosilicone rubber have excellent performance and are used and studied, but they are expensive. Therefore, it is necessary to develop new materials, processes and structures to meet the special performance requirements of special cables for the petroleum industry, such as higher oil resistance, wear resistance, aging resistance and tensile properties. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a special cable resistant to extreme environments, which can serve for a long time in an oily environment; at the same time, it has excellent oil resistance, wear resistance, aging resistance and tensile strength, and can adapt to the extreme environment in the oil industry.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A special cable resistant to extreme environments, comprising a sheath layer, an insulating layer and a conductive core from the outside to the inside, wherein the sheath layer is made of a sheath material, and the sheath material comprises the following components by weight: 40-60 parts of a modified ethylene-vinyl acetate copolymer, 35-90 parts of an elastomer, 30-50 parts of a modified filler, 15-25 parts of a plasticizer, 3-8 parts of POE-g-GMA, and 0.5-27 parts of an additive;

[0008] The modified ethylene-vinyl acetate copolymer is an ethylene-vinyl acetate copolymer filled with aminated halloysite nanotubes; the VA content of the ethylene-vinyl acetate copolymer is 20wt%~40wt%; the melt index under the conditions of 190℃ / 2.16kg is 2~6g / 10min; the melting point measured by the DSC method is 58~73℃;

[0009] The modified filler is a compound of calcium carbonate, white carbon black and diatomaceous earth in a mass ratio of 1:(4-6):(3-4) treated with a perfluorosilane coupling agent;

[0010] The elastomer is a compound of nitrile rubber, chlorosulfonated polyethylene rubber and polyurethane elastomer in a mass ratio of (2-4):(1-3):1; the Mooney viscosity of the chlorosulfonated polyethylene rubber is 40-50 ML (1+4) 100°C.

[0011] Halloysite, chemical composition is Al4[Si4O 10](OH)8·nH2O is a natural nano-hollow tubular aluminosilicate mineral; its crystal structure is a dioctahedral structure similar to kaolinite. Halloysite is ionized in water, so that its inner and outer layers have opposite charge distributions; the surface of halloysite contains a large number of Si-O bonds and Si-OH, which are negatively charged; while the inner layer contains Al-OH and Al-O bonds, which are positively charged. The special hollow tubular structure of halloysite has the effect of dispersing external stress and reducing stress concentration, which greatly enhances the tensile strength and tensile stress of ethylene-vinyl acetate copolymer. Secondly, the larger inner cavity space of halloysite makes it exhibit good thermal barrier effect, and the large amount of -OH on the tube wall causes it to undergo dehydration condensation under high temperature, thereby improving the aging resistance of modified ethylene-vinyl acetate copolymer and cable sheath materials.

[0012] Specifically, the Mooney viscosity of the chlorosulfonated polyethylene rubber can be obtained by testing according to the reference standard GB / T 1232.1-2016.

[0013] Specifically, the melt index of the ethylene-vinyl acetate copolymer is measured according to the test reference standard ISO 1133-2011, and the melting point is measured according to the test reference standard ISO 3146-2022.

[0014] Preferably, the perfluorosilane coupling agent includes at least one of nonafluorohexyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, perfluorooctyltrichlorosilane and heptadecafluorodecyltrimethoxysilane; and the plasticizer is trioctyl trioctanoate.

[0015] Perfluorosilane coupling agent is a kind of coupling agent containing CF bond and siloxane bifunctional group: the outer shell composed of F atoms surrounds the CC main chain into a complete cylinder, reducing the attraction between internal molecules, and the fluorocarbon functional groups arranged closely toward the outside have extremely low surface energy and extremely poor wettability; the siloxane groups contained release low molecular alcohols after hydrolysis, and the active silanols produced can chemically bond with the hydroxyl and oxygen-containing groups in the three fillers to form a self-assembled monomolecular fluorosilicone film layer on the surface of the inorganic material, thereby enhancing the dispersion stability of the mixed filler dispersion; and the hydrolysis rate is faster and more efficient than that of ethoxylated fluorosilane.

[0016] Preferably, the auxiliary agent includes one or more of 1-3 parts of dispersant, 3-7 parts of vulcanizer, 1-4 parts of co-vulcanizer, 2-6 parts of activator, 1-4 parts of antioxidant, and 0.5-3 parts of antioxidant.

[0017] Preferably, the dispersant is ethylene-vinyl acetate copolymer wax; the vulcanizing agent is diisopropylbenzene peroxide; the co-vulcanizing agent is dipentamethylenethiuram hexasulfide; the activator is selected from at least one of zinc oxide, stearic acid, zinc stearate, and calcium stearate; the antioxidant is a compound of 2,6-di-tert-butyl-4-methylphenol and nickel dibutyl dithiocarbamate in a mass ratio of 2:1; the antioxidant is a compound of the main antioxidant 168 and the auxiliary antioxidant DLTP in a mass ratio of 3:2.

[0018] Preferably, the sheath material also includes 10-25 parts of phosphorus-nitrogen compound flame retardant.

[0019] Preferably, the phosphorus-nitrogen type composite flame retardant is a composite system of piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 1:1.

[0020] In a specific embodiment, the preparation method of the modified filler is as follows: calcium carbonate, white carbon black and diatomaceous earth are mixed, added to an ethanol aqueous solution, and ultrasonically dispersed until uniform to obtain a suspension with a concentration of 12wt% to 20wt%; 0.2wt% to 10wt% of a perfluorosilane coupling agent equivalent to the total mass of the filler is added, and the pH value is adjusted to 3.5 with an appropriate amount of acetic acid; the temperature is raised to 60 to 90°C and stirred for 1-3h; after the reaction is completed, the suspension is centrifuged to obtain a precipitate, and washed with ethanol; and dried to obtain a modified filler.

[0021] In a specific embodiment, the preparation method of the modified ethylene-vinyl acetate copolymer is as follows: first, the halloysite nanotubes are dried to remove the crystal water; the dried halloysite nanotubes and the aminosilane coupling agent with a mass ratio of 10: (1~1.2) are added to a toluene solution, and condensed and refluxed at 60-90°C for 6~12h; after the reaction is completed, centrifugation is performed with anhydrous ethanol, and the precipitate is ultrasonically washed at least 3 times, and finally vacuum dried at 40~80°C for 6~12h to obtain the amino-halloysite nanotubes; the ethylene-vinyl acetate copolymer is added to the mixture The mixture is heated to melt at 140-160° C. in a mixer, and sodium hydroxide is added in an amount equivalent to 2wt% to 8wt% of the mass of the ethylene-vinyl acetate copolymer, and stirred at 60-75 rpm for 10-20 minutes; when the temperature drops to 80-100° C., the aminated halloysite nanotubes are added, and the mass of the aminated halloysite nanotubes is equivalent to 10-30wt% of the mass of the ethylene-vinyl acetate copolymer, and the mixture is stirred and kneaded for 25-50 minutes; after kneading, the mixture is dried at 80-100° C. to obtain a modified ethylene-vinyl acetate copolymer.

[0022] In a specific embodiment, the preparation method of the sheath material is as follows:

[0023] The polyurethane elastomer, nitrile rubber and chlorosulfonated polyethylene rubber are dried at 80-100°C for 6-12 hours, added into a high-speed mixer, mixed with modified ethylene-vinyl acetate copolymer at a high speed of 450-800 rpm, and then POE-g-GMA is added, mixed at a temperature of 90-120°C for 10-20 minutes to obtain a mixed rubber;

[0024] The mixed rubber, plasticizer and additive are mixed in an internal mixer for 3-5 minutes, and then the modified filler is added, and the mixing is continued for 5-15 minutes, and the mixer is stopped for unloading, wherein the mixer speed is 100-200 rpm and the temperature is 80-100° C.;

[0025] The kneaded mixture is sent to a twin-screw extruder granulator for extrusion molding, and the extruder screw speed is maintained at 90-150rpm and the temperature is maintained at 120-200°C; the extruded material is pressed and molded under the action of a flat vulcanizer to obtain the sheath material.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] The present invention provides a special cable resistant to extreme environments, wherein the sheath material uses three elastomers and modified ethylene-vinyl acetate copolymer as a common rubber system. First, the filling and modification of ethylene-vinyl acetate copolymer by halloysite nanotubes makes up for its deficiencies in tensile strength and aging resistance; at the same time, rigid chlorosulfonated polyethylene rubber, polyurethane elastomer and modified ethylene-vinyl acetate copolymer are blended to further enhance the comprehensive performance of the cable in terms of wear resistance and hydrocarbon oil corrosion resistance. In addition, nitrile rubber also plays the role of a compatibilizer, promoting the formation of a composite cross-linked network in the blended rubber system, increasing the cross-linking density, and further increasing the tensile stress of the cable.

[0028] The present invention introduces fluorine-containing chains in the form of inorganic filler modification, and while uniformly dispersing three inorganic fillers and increasing compatibility with rubber, gives the cable sheath material extremely low surface energy and extremely poor wettability; and controls the amount of perfluorosilane coupling agent to be 0.2wt%~10wt%, thereby obtaining a cable sheath layer with more excellent water-repellent, oil-repellent, anti-fouling and anti-adhesion properties, thereby further improving the cable's resistance to oil corrosion.

[0029] The present invention provides a special cable resistant to extreme environments, whose sheath material has the characteristics of excellent oil resistance and wear resistance, good aging resistance and tensile performance, and can be used to produce special cables such as logging cables, oil production cables, heating cables, etc. in the petroleum industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the infrared spectrum of halloysite before and after APTES amination. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0033] The sources of raw materials and production equipment for preparing cable sheath materials in each embodiment and comparative example are as follows:

[0034] Chlorosulfonated polyethylene rubber 1, brand CSM3304, Mooney viscosity 48 ML (1+4) 100°C, purchased from Foshan Weixunda New Material Technology Co., Ltd.;

[0035] Chlorosulfonated polyethylene rubber 2, grade 503, Mooney viscosity 57 ML (1+4) 100°C, purchased from Foshan Weixunda New Material Technology Co., Ltd.;

[0036] Ethylene-vinyl acetate copolymer 1: VA content 28wt%, melt index at 190℃ / 2.16kg is 3g / 10min, melting point measured by DSC method is 73℃, brand ELVAX 265, DuPont, USA;

[0037] Ethylene-vinyl acetate copolymer 2: VA content 40wt%, melt index at 190℃ / 2.16kg is 3g / 10min, melting point measured by DSC method is 58℃, brand ELVAX 40L-03, DuPont, USA;

[0038] Ethylene-vinyl acetate copolymer 3: VA content 18wt%, melt index at 190℃ / 2.16kg is 2.5g / 10min, melting point measured by DSC method is 88℃, brand ELVAX 460, DuPont, USA;

[0039] Ethylene-vinyl acetate copolymer 4: VA content 28wt%, melt index at 190℃ / 2.16kg is 25g / 10min, melting point measured by DSC method is 70℃, brand ELVAX 250, DuPont, USA;

[0040] Ethylene-vinyl acetate copolymer 5: VA content 28wt%, melt index at 190℃ / 2.16kg is 6g / 10min, melting point measured by DSC method is 75℃, brand ELVAX 260, DuPont, USA;

[0041] Nitrile rubber: acrylonitrile content 34wt%, Mooney viscosity (ML100℃(1+4)) 55, brand Therban3496, Lanxess, Germany;

[0042] Polyurethane elastomer: Brand A85C4957; HUNTSMAN from Germany;

[0043] POE-g-GMA, grafting rate 1%, Dongyuan County Ziheng Plastic Factory;

[0044] Curing agent: dicumyl peroxide (DCP), 52wt%<content≤100wt%, Hefei Tianjian Chemical Co., Ltd.;

[0045] Vulcanizing agent: dipentamethylenethiuram hexasulfide (DPTT), purity 98%, Shanghai Chengjin Chemical Co., Ltd.;

[0046] Activator: zinc stearate (zinc content 10.5wt%-11.5wt%), Shanghai Yunhe Material Technology Co., Ltd.; zinc oxide (purity 99.5%), Guangzhou Lida Rubber Raw Materials Co., Ltd.; the mass ratio of zinc stearate to zinc oxide is 2:1;

[0047] Toluene (AR), anhydrous ethanol (99%, AR), acetic acid, and sodium hydroxide were purchased from MacLean Reagent Company;

[0048] Antioxidant: 2,6-di-tert-butyl-4-methylphenol (264), Yantai Daoping Chemical Materials Co., Ltd.; nickel dibutyl dithiocarbamate (NBC), purity 99%, Hubei Jusheng Technology Co., Ltd.; the mass ratio of 264 to NBC is 2:1;

[0049] Flame retardant: piperazine pyrophosphate, 98% AR, Guangdong Yunxing Biotechnology Co., Ltd.; melamine polyphosphate, FR-MPP200, Guangzhou Yinyuan New Materials Co., Ltd.; the mass ratio of piperazine pyrophosphate to melamine polyphosphate is 1:1;

[0050] Dispersant: ethylene-vinyl acetate copolymer wax, viscosity 1200-1500 mPa·S, Luwax EVA3 Pulver, BASF;

[0051] Antioxidant: main antioxidant 168 and auxiliary antioxidant DLTP compounded in a mass ratio of 3:2; commercially available;

[0052] Plasticizer: trioctyl trioctanoate (TOTM), purity 97%, MacLean Reagent Company;

[0053] Heptadecafluorodecyltrimethoxysilane, purity 98%, Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;

[0054] Aminosilane coupling agent: 3-aminopropyltriethoxysilane APTES, Sigma Reagent Company;

[0055] Halloysite nanoclay (Al2O3·2SiO2·2H2O), (30-70)nm×(1-3) μ m, Sigma reagent company;

[0056] Diatomaceous earth, 325 mesh, silicon dioxide content 90wt%~92wt%, Changbai County Qingshanyuan Diatomaceous Earth Co., Ltd.;

[0057] Heavy calcium carbonate, 400 mesh, content ≥97wt%, Guangxi Helixin Mining Development Co., Ltd.;

[0058] White carbon black: a380, content 99.8wt%, Shandong Kasong New Materials Co., Ltd.;

[0059] Modified ethylene-vinyl acetate copolymer 1: The preparation method is as follows:

[0060] The halloysite nanotubes were dried at 90°C to remove the crystal water; 46 parts of the dried halloysite nanotubes and 4.73 parts of APTES were added to 50 mL of toluene solution, and condensed and refluxed at 60-90°C for 12 hours; after the reaction, the solution was centrifuged with anhydrous ethanol, and the precipitate was ultrasonically washed 3 times; finally, the solution was vacuum dried at 60°C for 12 hours to obtain the aminated halloysite nanotubes; the infrared spectra of the halloysite before and after the amination are shown in FIG. Figure 1 .

[0061] 100 parts of ethylene-vinyl acetate copolymer 1 were added to a mixer and heated at 160°C until melted, 4 wt% of sodium hydroxide was added, and stirred at 60 rpm for 20 minutes; then the temperature was lowered to 80°C, 18 parts of the aforementioned amino-treated halloysite nanotubes were added, and the mixture was stirred and kneaded for 40 minutes; after kneading, the mixture was dried at 80°C to obtain a modified ethylene-vinyl acetate copolymer.

[0062] Modified ethylene-vinyl acetate copolymer 2: The preparation method is the same as that of modified ethylene-vinyl acetate copolymer 1, except that ethylene-vinyl acetate copolymer 1 is replaced by ethylene-vinyl acetate copolymer 2;

[0063] Modified ethylene-vinyl acetate copolymer 3: The preparation method is the same as that of modified ethylene-vinyl acetate copolymer 1, except that ethylene-vinyl acetate copolymer 1 is replaced by ethylene-vinyl acetate copolymer 3;

[0064] Modified ethylene-vinyl acetate copolymer 4: The preparation method is the same as that of modified ethylene-vinyl acetate copolymer 1, except that ethylene-vinyl acetate copolymer 1 is replaced by ethylene-vinyl acetate copolymer 4;

[0065] Modified ethylene-vinyl acetate copolymer 5: The preparation method is the same as that of modified ethylene-vinyl acetate copolymer 1, except that ethylene-vinyl acetate copolymer 1 is replaced by ethylene-vinyl acetate copolymer 5;

[0066] Modified ethylene-vinyl acetate copolymer 6: The preparation method is the same as that of modified ethylene-vinyl acetate copolymer 1, except that the halloysite nanotubes are not modified by amino.

[0067] Modified filler 1: Weigh 100 parts of calcium carbonate, white carbon black, and diatomaceous earth in a mass ratio of 1:6:3, add them to 400 parts of ethanol aqueous solution (95 vol%), and ultrasonically disperse them at 300 W for 1 hour to obtain a 20 wt% suspension; add 2 parts of 17-fluorodecyl trimethoxysilane, adjust the pH value to 3.5 with an appropriate amount of acetic acid; heat to 60°C, and stir at 200 rpm for 2 hours. After the reaction is completed, the suspension is centrifuged, the precipitate is washed with alcohol, and finally dried at 80°C for 8 hours to constant weight to obtain modified filler 1.

[0068] Modified filler 2: The preparation method is similar to that of modified filler 1, except that the mass ratio of calcium carbonate, white carbon black and diatomaceous earth is 1:4:4.

[0069] Modified filler 3: The preparation method is different from that of modified filler 1, except that the mass ratio of calcium carbonate, white carbon black and diatomaceous earth is 1:8:1.

[0070] Modified filler 4: The preparation method is different from that of modified filler 1, except that the mass ratio of calcium carbonate, white carbon black and diatomaceous earth is 1:2:7.

[0071] Modified filler 5: The preparation method is similar to that of modified filler 1, except that no white carbon black is added, and the mass ratio of calcium carbonate to diatomaceous earth is 5:4.

[0072] Modified filler 6: The preparation method is the same as that of modified filler 1, except that no calcium carbonate is added, and the mass ratio of white carbon black to diatomaceous earth is 5:4.

[0073] Modified filler 7: The preparation method is similar to that of modified filler 1, except that diatomaceous earth is not added, and the mass ratio of calcium carbonate to white carbon black is 1:9.

[0074] Modified filler 8: The preparation method is the same as that of modified filler 1, except that heptadecafluorodecyltrimethoxysilane is not added.

[0075] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0076] Embodiment 1~5

[0077] A special cable resistant to extreme environments includes a sheath layer, an insulating layer and a conductive core from the outside to the inside, wherein the sheath layer is made of a sheath material, wherein the sheath material components are shown in Table 1, and the preparation method is as follows:

[0078] The polyurethane elastomer, nitrile rubber and chlorosulfonated polyethylene rubber were dried at 80°C for 12 h and then added into a high-speed mixer, mixed with modified ethylene-vinyl acetate copolymer at a high speed of 600 rpm, and then POE-g-GMA was added and mixed at a temperature of 110°C for 15 min to obtain a mixed rubber;

[0079] The above-mentioned mixed rubber, plasticizer and additive were mixed in an internal mixer for 4 minutes, and then the modified filler was added, and the mixing was continued for 10 minutes, and the mixer was stopped for unloading; wherein the mixer speed was 160 rpm and the temperature was 95°C;

[0080] The kneaded mixture is sent to a twin-screw extruder granulator for extrusion molding, and the extruder screw speed is maintained at 120 rpm and the temperature is maintained at 150° C. The extruded material is pressed and molded under the action of a flat vulcanizer to obtain the sheath material.

[0081] Table 1 Sheath material composition of Examples 1 to 5 (parts by weight)

[0082]

[0083] Comparative Examples 1 to 14

[0084] The preparation method is the same as that of Examples 1 to 5, except that the composition and weight of the sheath material are different, as shown in Table 2.

[0085] Table 2 Comparative Example Sheath Material Composition (Parts by Weight)

[0086]

[0087] Test Case

[0088] In order to more clearly illustrate the present invention, the performance of the cable sheath material obtained in the embodiment and the comparative example is tested by the following test; 3 parallel experiments are carried out for each group of samples, and the results are averaged. The test methods of each index are as follows:

[0089] (1) Tensile strength and 100% elongation stress: The maximum load per unit cross section when the specimen is stretched to fracture is the tensile strength. The load per unit area when the specimen is stretched to 100% of a certain strain is the 100% elongation stress.

[0090] According to the national standard GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", the test was carried out using a universal testing machine, where the applied tensile rate was 250 mm·min -1 , the test temperature is 25℃±3℃. The effective part of the sample is 25mm in length, 6mm in width and 1mm in thickness.

[0091] (2) Wear performance test: The test is carried out according to the standard GB / T 3960-2016 "Plastic Sliding Friction and Wear Test Method". The lower the wear rate, the better the wear resistance.

[0092] (3) Xenon lamp artificial accelerated aging test: The national standard GB / T 3512-2014 "Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber" is used to determine the aging resistance. The test temperature is 65℃±3℃ and the relative humidity is 65%±3%. After 1000 hours of xenon lamp irradiation, the change rate of tensile strength is tested and the appearance is judged to see if there is any cracking.

[0093] (4) Oil resistance:

[0094] In view of the special extreme environment of the petroleum industry, the test was carried out according to the national standard GB / T 1690-2010 "Test Method for Liquid Resistance of Vulcanized Rubber or Thermoplastic Rubber" using a variety of test oil test processes. Test oil: 2# standard oil (IRM902), 3# standard oil (IRM903). Each group of samples was made into a type II dumbbell bar with a width of 4 mm and a gauge length of 25 mm, and immersed in a beaker filled with each test oil. The temperature was uniformly set to 100℃ and the immersion time was 72h. The tensile strength and mass were tested before and after oil immersion, and the change rates were calculated.

[0095] The calculation formula of the change rate of tensile strength before and after oil immersion is shown in formula (1):

[0096] (1)

[0097] Wherein, Δσ is the change rate of tensile strength before and after oil immersion (when Δσ>0, the tensile strength increases after oil immersion; when Δσ<0, the tensile strength decreases after oil immersion), %; σ1 is the tensile strength of the sample before oil immersion, MPa; σ2 is the tensile strength of the sample after oil immersion, MPa;

[0098] The swelling ratio ΔV before and after oil immersion is calculated according to formula (2):

[0099] (2)

[0100] Wherein, ΔV is the swelling change of the sample before and after oil immersion (when ΔV>0, the volume of the material increases after oil immersion; when ΔV<0, the volume of the material decreases after oil immersion), %; m1 is the mass of the sample before oil immersion, g; m2 is the mass of the sample after oil immersion, g; m3 is the mass of the sample in water before oil immersion, g; m4 is the mass of the sample in water after oil immersion, g.

[0101] Table 3 Performance test results of the embodiments and comparative examples

[0102]

[0103] The present invention provides a special cable resistant to extreme environments, and its sheath material has the advantages of high tensile strength, excellent wear resistance, good aging resistance, good oil resistance, etc. The tensile strength is greater than 30MPa, and it is resistant to corrosion by various oils, highlighting its wide range of oil resistance.

[0104] It can be seen from Example 3, Example 5 and Comparative Examples 1 to 5 that under the compounding range of the mass ratio of calcium carbonate, white carbon black and diatomaceous earth of 1:(4~6):(3~4), the particle size gradation of the modified filler is optimal, the filler is more dense and uniform when mixed, and the mechanical properties and oil resistance are good. When there is too little or no white carbon black in Comparative Examples 2 to 3, there are too many gaps between the micron-sized diatomaceous earth and calcium carbonate particles, resulting in defects in the filler, which is not conducive to the overall stability of the filler system; in Comparative Example 1, there is too much white carbon black, or it is easy to self-polymerize to make the fluorinated silane coupling agent cross-link itself, or occupy too many bonding sites with the fluorinated silane coupling agent, so that large particles of calcium carbonate and diatomaceous earth cannot fully contact and interact with the coupling agent. In Comparative Example 4, the filler lacks calcium carbonate, and the calcium carbonate particles have good chemical stability. On the one hand, it plays a role in optimizing the particle size distribution and density in the mixed filler; on the other hand, it can also inhibit the self-polymerization and mutual aggregation of white carbon black and diatomaceous earth. In comparative example 5, diatomaceous earth is not added. The hydroxyl groups on the surface of the white carbon black particles are highly polar. In addition to having greater reactivity with the perfluorosilane coupling agent, they are also very easy to combine with each other to form aggregates; thus, the filler system is insufficiently dispersed, which further leads to performance loss of the sheath material.

[0105] In Comparative Example 6, the mixed filler is not modified by the perfluorosilane coupling agent, resulting in a significant reduction in the compatibility and dispersibility of the filler, and a significant decrease in the mechanical properties and oil resistance of the sheath material.

[0106] In Comparative Examples 7 and 8, only one elastomer is added, and the tensile strength, wear resistance, aging resistance and oil resistance are all poor. This is because when there is too much nitrile rubber, the performance is poor in a high temperature environment, and it is easy to soften and lose elasticity. When there is too much polysulfonated vinyl chloride rubber, the viscosity of the system increases, which easily leads to uneven dispersion of fillers, etc., thereby increasing quality defects such as cracks and bubbles.

[0107] Among them, it can be seen from Examples 3 to 4 and Comparative Examples 9 to 11 that when the VA content of the ethylene-vinyl acetate copolymer is 20wt% to 40wt%, the melt index under 190°C / 2.16kg is 2 to 6g / 10min, and the melting point measured by the DSC method is 58 to 73°C, the obtained sheath material has the best comprehensive properties such as tensile strength, wear resistance, aging resistance and oil resistance. This is because when the melt index of ethylene-vinyl acetate copolymer is too high, the molecular chain is shorter, and the mechanical properties and oil resistance are poor; when the melting point of ethylene-vinyl acetate copolymer is too high, its crystallinity is higher, the flexibility is poor, and the processing temperature is higher. It is more likely to crack and break under bending, stretching and other conditions, which makes it easy to enter oil and swell; ethylene-vinyl acetate copolymer with low VA content has poor polarity and insufficient compatibility with other polymers; and the molecular weight distribution is narrower, the degree of cross-linking is worse, and the tensile strength, chemical resistance, heat deformation resistance and other properties of the cable sheath material are reduced, but the effect on oil resistance is not significant.

[0108] It can be seen from Example 3 and Comparative Example 14 that when the Mooney viscosity of the chlorosulfonated polyethylene rubber is 40~50 ML (1+4) at 100°C, the sheath material has the best comprehensive properties such as tensile strength, wear resistance, high temperature resistance and oil resistance. When the viscosity is too high, uneven mixing with other components is likely to occur, affecting the appearance and mechanical properties of the cable.

[0109] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A special cable resistant to extreme environments, comprising a sheath layer, an insulating layer and a conductive core from the outside to the inside, characterized in that: The sheath layer is made of a sheath material, and the sheath material includes the following components in parts by weight: 40-60 parts of modified ethylene-vinyl acetate copolymer, 35-90 parts of elastomer, 30-50 parts of modified filler, 15-25 parts of plasticizer, 3-8 parts of POE-g-GMA, and 0.5-27 parts of additives; The modified ethylene-vinyl acetate copolymer is an aminated halloysite nanotube-filled ethylene-vinyl acetate copolymer; the ethylene-vinyl acetate copolymer has a VA content of 20wt% to 40wt%, a melting point of 58 to 73°C, and a melt index of 2 to 6g / 10min at 190°C / 2.16kg; The preparation method of the modified ethylene-vinyl acetate copolymer is as follows: first, drying the halloysite nanotubes to remove crystal water; adding the dried halloysite nanotubes and aminosilane coupling agent in a mass ratio of 10:(1-1.2) to a toluene solution, condensing and refluxing at 60-90° C. for 6-12 hours; after the reaction is completed, centrifuging with anhydrous ethanol, ultrasonically washing the precipitate for at least 3 times, and finally vacuum drying at 40-80° C. for 6-12 hours to obtain the aminated halloysite nanotubes; adding the ethylene-vinyl acetate copolymer to the The mixture is heated to 140-160° C. in a mixer until it is melted, and sodium hydroxide is added in an amount equivalent to 2wt% to 8wt% of the mass of the ethylene-vinyl acetate copolymer, and stirred at 60-75 rpm for 10-20 minutes; when the temperature drops to 80-100° C., the amino-treated halloysite nanotubes are added in an amount equivalent to 10-30% of the mass of the ethylene-vinyl acetate copolymer, and stirred and kneaded for 25-50 minutes; after kneading, the mixture is dried at 80-100° C. to obtain a modified ethylene-vinyl acetate copolymer; The modified filler is a compound of calcium carbonate, white carbon black and diatomaceous earth in a mass ratio of 1:(4-6):(3-4) treated with a perfluorosilane coupling agent; The elastomer is a compound of nitrile rubber, chlorosulfonated polyethylene rubber and polyurethane elastomer in a mass ratio of (2-4):(1-3):1; the Mooney viscosity of the chlorosulfonated polyethylene rubber is 40-50 ML (1+4) 100°C.

2. The special cable according to claim 1, characterized in that: The perfluorosilane coupling agent includes at least one of nonafluorohexyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, perfluorooctyltrichlorosilane and heptadecafluorodecyltrimethoxysilane; and the plasticizer is trioctyl trioctanoate.

3. The special cable according to claim 1, characterized in that: The auxiliary agent includes one or more of 1-3 parts of dispersant, 3-7 parts of vulcanizer, 1-4 parts of co-vulcanizer, 2-6 parts of activator, 1-4 parts of antioxidant and 0.5-3 parts of antioxidant.

4. The special cable according to claim 3, characterized in that: The dispersant is ethylene-vinyl acetate copolymer wax; the vulcanizing agent is diisopropylbenzene peroxide; the co-vulcanizing agent is dipentamethylenethiuram hexasulfide; the activator is at least one selected from zinc oxide, stearic acid, zinc stearate, and calcium stearate; the antioxidant is a compound of 2,6-di-tert-butyl-4-methylphenol and nickel dibutyl dithiocarbamate in a mass ratio of 2:1; the antioxidant is a compound of the main antioxidant 168 and the auxiliary antioxidant DLTP in a mass ratio of 3:

2.

5. The special cable according to claim 1, characterized in that: The sheath material also includes 10-25 parts of phosphorus-nitrogen compound flame retardant.

6. The special cable according to claim 5, characterized in that: The phosphorus-nitrogen type composite flame retardant is a composite system of piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 1:

1.

7. The special cable according to claim 1, characterized in that: The preparation method of the modified filler is as follows: calcium carbonate, white carbon black and diatomaceous earth are mixed, added into an ethanol aqueous solution, and ultrasonically dispersed until uniform to obtain a suspension with a concentration of 12wt% to 20wt%; 0.2wt% to 10wt% of a perfluorosilane coupling agent equivalent to the total mass of the filler is added, and the pH value is adjusted to 3.5 with an appropriate amount of acetic acid; the temperature is raised to 60 to 90° C. and stirred for 1 to 3 hours; after the reaction is completed, the suspension is centrifuged to obtain a precipitate, and washed with ethanol; and dried to obtain the modified filler.

8. The special cable according to claim 1, characterized in that: The preparation method of the sheath material is as follows: The polyurethane elastomer, nitrile rubber and chlorosulfonated polyethylene rubber are dried at 80-100°C for 6-12 hours, added into a high-speed mixer, mixed with modified ethylene-vinyl acetate copolymer at a high speed of 450-800 rpm, and then POE-g-GMA is added, mixed at a temperature of 90-120°C for 10-20 minutes to obtain a mixed rubber; The mixed rubber, plasticizer and additive are mixed in an internal mixer for 3-5 minutes, and then the modified filler is added, and the mixing is continued for 5-15 minutes, and the mixer is stopped for unloading, wherein the mixer speed is 100-200 rpm and the temperature is 80-100° C.; The kneaded mixture is sent to a twin-screw extruder granulator for extrusion molding, and the extruder screw speed is maintained at 90-150rpm and the temperature is maintained at 120-200°C; the extruded material is pressed and molded under the action of a flat vulcanizer to obtain the sheath material.

Citation Information

Patent Citations

  • Cold-resistant data transmission cable

    CN111627604A

  • Slurry-resistant marine cable

    CN118213116A